PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI DAERAH TEMPAT TINGGALKU MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING - Eka Sakti Ismulya; R.Teti Rostikawati; Siti Nurjanah (STKIP Subang, 2023)
The purpose of the study is to improve learning outcomes for students by using the Project Based Learning learning model for grade IV-A students at SDN Bondongan Bogor City in the second semester of the 2022/2023 academic year. The research used was a qualitative descriptive Collaborative Classroom Action Research (PTKK) using a qualitative approach and validated using a quantitative approach with data collection at SDN Bondongan Bogor City. The subjects of the study were students of class IV-A SDN Bondongan Bogor City with a total of 26 students, 12 women and 14 men. The object of this study is the improvement of student learning outcomes in Theme 8: My Area of Residence in Natural Sciences (Science) subjects using the Project Based Learning model. This research is carried out in two cycles and through four stages which include: planning, implementation, observation and reflection. Data is obtained through observation, implementation of learning, direct tests and documentation. The results of the study show that the application of the Project Based Learning model can improve student learning outcomes. The increase in student learning outcomes is measured from the results of the evaluation of cycle I and cycle II with an increase in the learning outcomes of students who have achieved learning outcomes, namely in cycle I by 62% (16 students) and in cycle II by 88% (23 students). The results of research in class IV-A at SDN Bondongan Bogor City have been achieved well because there is an increase in learning outcomes by applying the Project Based Learning model.